The Implementation Of Treffinger Model To Improve Students’ Ability In Determining The Main Idea Of Paragraph At Sma Swasta Galih Agung At Academic Year 2016/2017 - Retno Sayekti (UIN Sumatera Utara, 2018)
This research is aimed at improving the students’ ability in determining the main idea of paragraph by using Treffinger model. The subject of this research was tenth grade of Senior High School at SMA Swasta Galih Agung Lau Bakeri Deli Serdang in 2017 academic year. This study was conducted by using classroom action research. The research is done in three cycles, where in every cycle consists of four steps, there are planning, acting, observing, and reflecting. Cycle I consists of one meeting and also for cycle II and cycle III. The instruments of data collection used in this research are: interview sheet, obeservation sheet, diary note, and documentation (photography evidence). The finding of the research showed that: (1) Students’ ability in determining the main idea of paragraph taught by Treffinger Model is improved. (2) The Treffinger model is proved to be effective in improving the students’ ability in determining the main idea of paragraph in tenth grade (3rd class of experiment) of Senior High School at SMA Swasta Galih Agung in 2017 academic year by some modifications on: a) teacher’s attitude who nerveous in teaching b) teacher’s carefulness in writing vocabulary c) teacher’s attitude in conveying the lesson and d) teacher’s class management.Key Word: Treffinger Model, Students’ Ability in Determining the Main Idea of Paragraph